THE TECHNOLOGY OF DEVELOPING HARMONIC HEARING - Zavadska, Galina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In Latvia, the development of harmonic hearing takes an important place in the process of training pre-service music teachers, because a music teacher is a conductor of a school choir or a conductor of some other choir collective. The issues relating to the system of properties of harmonic musical hearing have been highlighted in a range of scientific works by different authors (Teplov, 1947; Sloboda, 1988; Petrushin, 1997). However, at present the understanding of the nature and ways of developing harmonic hearing is sometimes quite controversial. This, first of all, can be attributed to the complexity of the interrelations between harmonic hearing and general psychic processes: perception, presentation, reproduction, memory, and thinking. The interconnectedness of general human and specific, individual qualities makes this problem difficult to study. The solution of the problem is made difficult by the fact that a collective teaching at sol-fa classes in a higher education establishment often conflicts with learners’ individual peculiarities and problems of developing their harmonic hearing. Within the frame of the case study the technology of developing harmonic hearing based on the strategy of experiential learning (model by David Kolb, 1984) has been worked out. The presented technology is grounded on individual students’ learning styles and on the author’s model of developing harmonic hearing (Zavadska, 2012b).